(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2020)
A specimen of Dempo Paris Peacock Papilio paris dempo Okano, 1988 (Lepidoptera: Rhopalocera: Papilionidae) has been caught and collected on 5 February 2020 in lower Dempo mountain, South Sumatra province, Indonesia. This butterfly was preserved for a scientific purpose, and the specimen deposited to biological museum of Department of Biology of Sriwijaya Unversity, with collection number Musbio/En/Coll.02.05022020. After preserved, the specimen was immediately identified using selected references. Recent finding of P. paris dempo is a rediscovery for this rare and endemic butterfly in Â its habitat after 32 years break (1988 to 2020). Based on this specimen, status of P. paris dempo is revisited.